2018
DOI: 10.1016/j.polymertesting.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between process and silica dispersion/distribution into composite: Impact on mechanical properties and Weibull statistical analysis

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Silica was also sonicated in acetone for 10 minutes. In a previous paper authors confirmed that the sonication time is particles size dependent: smaller particles need higher sonication time to be well dispersed [34]. Moreover, a higher level of rate incorporation necessitate again more sonication time.…”
Section: Preparation Of Pmma/silica Compositesmentioning
confidence: 82%
“…Silica was also sonicated in acetone for 10 minutes. In a previous paper authors confirmed that the sonication time is particles size dependent: smaller particles need higher sonication time to be well dispersed [34]. Moreover, a higher level of rate incorporation necessitate again more sonication time.…”
Section: Preparation Of Pmma/silica Compositesmentioning
confidence: 82%
“…The shape of the distribution curve is usually not the symmetrical Gaussian form but is skewed in Figure 3b. The F w values are meaning the median rank [25], and the median rank has no dimension. The F w determined according to the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…5b. The FM value means the median rank, which is dimensionless [29]. The FM can be determined with the following equation (Eq.…”
Section: Mechanical Property Analysismentioning
confidence: 99%